Tafsir Tarbawi terhadap Surah Al-Mumtahanah Ayat 8–9: Pendidikan Karakterdalam Konteks Hubungan Sosial - Moh. Nasir (Hikamatzu | Journal of Multidisciplinary, 2025)
This research aims to interpret Tarbawi's interpretation of Surah Al-Mumlahanah Verses 8–9: Character Education in the Context of Social Relations. The method used in this research is a literature review. Tarbawi's Tafsir findings on Surah Al-Mumlahanah verses 8–9 emphasize the importance of the character of education in forming just, tolerant and civilized social attitudes in social life. These verses teach that Islam does not prohibit its followers from doing good and being fair to non-Muslims who do not fight or expel Muslims, and even encourage the realization of harmonious social relations. On the other hand, Islam strictly prohibits building loyalty and closeness with parties who are hostile to and oppress Muslims. From the perspective of Tafsir Tarbawi, these values ​​are an important basis for the character of education, especially in forming individuals who are able to distinguish between compassion and the principle of firmness, as well as upholding the values ​​of justice, empathy and wisdom in social interactions across religions and cultures.